Efficacy of newer medications for lower urinary tract symptoms attributed to benign prostatic hyperplasia: a systematic review. (2nd January 2019) - MacDonald, Roderick; Brasure, Michelle; Dahm, Philipp; Olson, Carin M.; Nelson, Victoria A.; Fink, Howard A.; Risk, Michael C.; Rwabasonga, Bruce; Wilt, Timothy J.
Abstract: We conducted a systematic review to evaluate the efficacy and adverse effects of newer drugs used to treat lower urinary tract symptoms (LUTS). The drugs were either Food and Drug Administration (FDA) approved for benign prostatic hyperplasia (BPH) or not FDA approved for BPH but have been evaluated for treatment of BPH since 2008. We searched bibliographic databases through September 2017. We included randomized controlled trials (RCTs) lasting one month or longer published in English. Outcomes of interest were LUTS assessed by validated measures. Efficacy was interpreted using established thresholds indicating clinical significance that identified the minimal detectable difference. Twenty-three unique, generally short-term, RCTs evaluating over 9000 participants were identified. Alpha-blocker silodosin and phosphodiesterase type 5 inhibitor tadalafil were more effective than placebo in improving LUTS (moderate strength evidence) but these drugs had more adverse effects, including abnormal ejaculation (silodosin). Anticholinergics were only effective versus placebo when combined with an alpha-blocker. Evidence was generally low strength or insufficient for other drugs. Evidence was insufficient to assess long-term efficacy, prevention of symptom progression, need for surgical intervention, or long-term adverse effects. Longer trials are needed to assess the effect of these therapies on response rates using established minimal detectable difference thresholds, disease progression, and harms.